A Functional Genetic Variant at the C-Reactive Protein Promoter (rs3091244) Is Not Associated With Cancer Risk in a Chinese Population - Wang, Ming-Yu; Zhou, Hai-Hong; Zhang, Chun-Miao; Su, Hai-Xiang; Li, Shuo-Lei; Ji, Shang-Rong; Liu, Enqi; Wu, Yi (Frontiers in Immunology, 2020)
Background: The association of genetically elevated levels of circulating C-reactive protein (CRP) with cancer risk has been extensively investigated in European populations; however, there are conflicting conclusions. The tri-allelic rs3091244 is a functionally validated genetic variant, and its allelic frequencies differ significantly between European and Asian populations. Here, we examined the association of rs3091244 with cancer risk in a Chinese population. Methods: rs3091244 was genotyped by Sanger sequencing in 4,971 cancer cases and 2,485 controls. The rs1205 and rs2794521 gene variants were also genotyped using TaqMan assays in subgroups. Results: No association was detected between the genotyped CRP variants and cancer risk, with or without distinguishing cancer types, suggesting that circulating CRP is not causally involved in tumorigenesis in Chinese populations.